Effect of Microbial Consortia on Photosynthetic Efficiency of Arabidopsis thaliana under drought stress - Hazem M. Kalaji (Science Faculty of Chiang Mai University, 2019)
Photosynthetic efficiency of Arabidopsis thaliana plants has been investigated under drought stress conditions by several studies, but not in response to effective microorganisms (EM) application. Thus, our study aims to examine the effect of EM on growth and photosynthetic efficiency of Arabidopsis thaliana under water stress condition. Arabidopsis plants were treated with 3 EM concentrations (1, 5 and 10% v/v) on the same day of drought stress application. Another 2 experimental variants/combinations were also provided: control treatment (watered plants and without EM) and drought treatment (non-watered plants and without EM). After 2 weeks of drought application, photosynthetic efficiency, fresh and dry weight of Arabidopsis plants were measured and compared. Based on the data obtained from chlorophyll fluorescence measurements, the results showed negative effect of water stress on photosynthesis efficiency of Arabidopsis plants. This was confirmed by a notable decrease of fresh and dry mass of Arabidopsis plants exposed to drought. EM application enhanced plants tolerance to drought. That was proved by the increase of chlorophyll content and photosynthetic efficiency. The highest increase of chlorophyll fluorescence parameters was observed in stressed plants treated with EM concentration 1% v/v. Our research indicated that, EM treatment caused a stimulation of photosynthetic efficiency of Arabidopsis plant due to enhancement of energy transfer efficiency within photosystem II (PSII) under drought stress.